Empowering the Marginalized through the Halal Industry in Indonesia: A Systematic Literature Review - Nuryanto, Uli Wildan; Basrowi, Basrowi; Quraysin, Icin; Pratiwi, Ika; Utami, Pertiwi (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study aims to conduct a systematic literature review on the themes of equality and social justice for people with disabilities in Indonesia, with a specific focus on their intersection with community empowerment within the halal industry. Using empirical evidence and bibliometric analysis, the review applies the keywords